Melatonin inhibits amphetamine-induced nitric oxide synthase mRNA overexpression in microglial cell lines - Jiraporn Tocharus (2018)
Amphetamine (AMPH) derivatives are the most commonly abused drugs. Chronic or intermittent AMPH abuse may create temporary or permanent disturbances in the dopaminergic system of the brain that may predispose individuals to Parkinsonism. AMPH induces a massive release of dopamine from synaptic vesicles and then generates reactive oxygen species (ROS). Furthermore, nitric oxide (NO), produced in the central nervous system (CNS) mediated by the activation of microglia, appears to play a critical role in stress-induced brain damage. In the present study, we examined the involvement of NO in the neurotoxic effects of AMPH, to investigate the hypothesis that altered nitric oxide synthase (NOS) function was involved. AMPH at a concentration of 0.4-3.2 mM has a cytotoxic effect on highly aggressively proliferating immortalized (HAPI) cells, a rat microglial cell line. The effect of AMPH on increasing inducible NOS (iNOS) mRNA in HAPI microglial cells is concentration-dependent. Pretreatment with either S-methylisothiourea (S-MT), a selective iNOS inhibitor, or melatonin, a major secretory product of pineal gland, counteracted the over expression of iNOS induced by AMPH in a concentration-dependent manner. The induction of iNOS by AMPH in microglial cells could be an important source of NO in CNS inflammatory disorders associated with the death of neurons and oligodendrocytes. Administration of exogenous melatonin will be beneficial, as it reduces iNOS mRNA expression, and may, therefore, be able to be used as a neuroprotective agent in toxicity induced by AMPH or other immunogens. © 2008 Elsevier Ireland Ltd. All rights reserved.